Meckel's diverticulum with intussusception in a 5-year-old patient: Ultrasound as the key to diagnosis. A case report - Krzysztof Balawender; Iwona Kucharska-Miąsik; Maksymilian Kłosowicz; Wiktoria Florek; Edward Clarke; Artur Derlatka; Magdalena Szatny-Kiedrzyńska; Andrzej Żytkowski (Elsevier, 2024)
Background: Meckel's diverticulum is one of the most common congenital malformations of the gastrointestinal tract. About three-fourths of Meckel's diverticulum are located in the distance ranging from 40 cm to 100 cm from the ileocecal valve. Most cases are lined with heterotopic mucosa (e.g., gastric, pancreatic, jejunal). Many cases are asymptomatic. Aim: This case report aims to present an ultrasound image for intussusception caused by the anatomical anomaly, namely Meckel's diverticulum. The article was written to integrate fundamental knowledge of anatomical variations or anomalies with clinical context. Case description: A 5-year-old girl previously diagnosed with obesity came to the hospital with severe abdominal pain. The abdomen, on palpation examination, was tender and painful. Diagnosis of intussusception was initially based on the history, clinical symptoms, and ultrasound imaging. The girl was finally qualified for surgery. During the procedure, the bowel invagination was performed, and Meckel's diverticulum was removed. The intestine was double-layered and intraoperatively confirmed intussusception with Meckel's diverticulum. Conclusions: Knowledge of anatomical anomalies is significant for practitioners. Meckel's diverticulum may be the cause of invagination intestines. CT or MRI is the test of choice when intussusception is suspected during a proliferative disease.